Some Results in the CAPM with Nontraded Endowments - Oh, Gyutaeg (Management Science, 1996)
The paper establishes a positive security market line in the CAPM with nontraded endowments. The effects of a market structure change on the security market line are analyzed when the equilibrium allocation is affected by the change.